THE USE OF DIALOGUE TECHNIQUE IN SPEAKING AT SMP TAHFIDZ PAMEKASAN - Yuni Sriharlinda (Universitas Madura, 2021)
The dialogue is good way to get students practice saying target language. It also helps the students become more active to talk each other in teaching learning process. The researcher used descriptive qualitative research. The participant of the study were the English teacher and the students of SMP Tahfidz Pamekasan that consisted of 16 students. In collecting the data, the researcher uses observation, and interview. From the result of observation and interview, this research showed the implementation of dialogue technique. The teacher implement the dialogue with presentation of brief dialogue or several mini dialogue, oral practice of each utterances in the dialogue, question and answer based on the dialogue topic and situation in the dialogue, and evaluation of learning. The response with the highest percentage is interested that is 43,75 % with the seven participants. The second place is 31,25 % of the respondents or five participants which expressed hesitation, and 25% of respondents or four students who did not interested to the dialogue technique.